О природе кавитационных явлений в процесах получения синтетического топлива - Сурду, Н. В.; Тарелина, А. А.; Ковалев, А. С.; Слоневская, А. В.; Сивернюк, В. В. (НТУ "ХПИ", 2008)
The model of the mechanism of occurrence of the cavitations bubble in water systems is offered. In a basis of model is the guess of the uniform nature of the plastic derisions arising in metals and fluids. The analysis of kinetics of vaporous filling of a cavitations cavity has been executed.
Keywords: генерация тепла; каветационная каверна; насыщенный пар; адиабатическое сжатие